Value Relevance Human Capital Information on the Annual Report of Indonesia Listed Companies - Yie Ke Feliana; Ester Novita (Jurnal Keuangan dan Perbankan, 2018)
Human resources at the companies in Indonesia should be an important focus for investors, due to the general complaints of low labor productivity compared to other countries. This study aimed to investigate the value relevance of human capital disclosure and changes of human capital disclosure to share price and share return on listed companies at Indonesia Stock Exchange from all industrial sectors in 2016. Human capital information measured by word counting of information related to human capital in the firm annual report. The results showed that the disclosure information of human capital was value relevant with share price but only from qualification/ competencies category. For the disclosure changes in human capital, the information did not show any significant effect to return per share. Thus, generally Indonesia investors only focus on information on qualification/competency human resources in companies at that time, other information was ignored.JEL Classification: G11, G14, J24DOI: https://doi.org/10.26905/jkdp.v22i4.1945